Sketch for War, painting in the Museum of Picardy at Amiens - Pierre Puvis de Chavannes (Wikimedia Commons, 1861)
Notice iconographique issue de Wikimedia Commons. Titre: Sketch for War, painting in the Museum of Picardy at Amiens. Drawing | Drawings
Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; illustration